Improvement of the electron collection efficiency in porous hematite using a thin iron oxide underlayer: towards efficient all-iron based photoelectrodes. Issue 44 (19th October 2015) - Dalle Carbonare, Nicola; Carli, Stefano; Argazzi, Roberto; Orlandi, Michele; Bazzanella, Nicola; Miotello, Antonio; Caramori, Stefano; Bignozzi, Carlo A.
Abstract : By combining different iron oxide morphologies, the interfacial selectivity towards charge carriers generated in sol–gel hematite photoelectrodes is improved. Abstract : Different approaches have been explored to increase the water oxidation activity of nanostructured hematite (α-Fe2 O3 ) photoanodes, including doping with various elements, surface functionalization with both oxygen evolving catalysts (OEC) and functional overlayers and, more recently, the introduction of ultrathin oxide underlayers as tunneling back contacts. Inspired by this latter strategy, we present here a photoanode design with a nanometric spin-coated iron oxide underlayer coupled with a mesoporous hematite film deposited by electrophoresis. The electrodes equipped with the thin underlayer exhibit a four-fold improvement in photoactivity over the simple hematite porous film, reaching a stable photocurrent density of ca. 1 mA cm −2 at 0.65 V versus the saturated calomel electrode (SCE) at pH 13.3 (NaOH 0.1 M) under air mass (AM) 1.5G illumination. A further improvement to 1.5 mA cm −2 is observed after decoration of the hematite surface with a Fe(iii )-OEC. These results demonstrate that by combining different iron oxide morphologies, it is possible to improve the selectivity of the interfaces towards both electron collection at the back contact and hole transfer to the electrolyte, obtaining an efficient all-iron based photoelectrode entirely realized with simple wet solution scalable procedures.